Elevated effluent potassium concentrations predict the development of postreperfusion hyperkalemia in deceased liver transplantation: a retrospective cohort study - Liang Zhang; Fu-Shan Xue; Ming Tian; Zhi-Jun Zhu (BMC Anesthesiology, 2022)
Abstract Background Postreperfusion hyperkalemia (PRHK) has garnered increasing attention in regard to deceased liver transplantation (LT), especially for LT using the expanded criteria donor grafts. However, the impact of the effluent potassium (eK+) concentration on PRHK has been largely overlooked. We evaluated whether elevated eK+ concentrations are associated with PRHK in deceased LT. Methods In this single-institution, retrospective cohort study, we included all adults who underwent deceased LT with intraoperative eK+ concentration monitoring between November 2016 and December 2018. The eK+ concentrations were obtained from the effluent samples collected following a standard portal vein flush. PRHK was defined as any serum potassium (sK+) level of > 5.5 mmol/L following reperfusion. Logistic regression was performed to identify predictors for PRHK, and linear regression was used to examine predictors of the maximum percentage increase in the sK+ level following reperfusion. Results Of the 86 patients who met the inclusion criteria, 54 (62.8%) developed PRHK. Independent predictors for PRHK included greater graft weight (OR 1.283 [95% CI 1.029–1.599] per 100 g, P = 0.027), an elevated eK+ concentration (OR 1.291 [95% CI 1.068–1.561] per mol/L, P = 0.008), and a higher sK+ level before reperfusion (OR 4.459 [95% CI 1.543–12.884] per mol/L, P = 0.006). An eK+ concentration of more than 6.9 mmol/L had a sensitivity of 59.26% and a specificity of 78.12% for predicting PRHK (area under the receiver operating characteristic curve, 0.694). Multiple linear regression analyses indicated that the eK+ and sK+ levels before reperfusion were significant predictors of the maximum percentage increase in the sK+ level following reperfusion. In addition, PRHK was associated with an increased risk of postreperfusion significant arrhythmias, severe postreperfusion syndrome, and postoperative early allograft dysfunction. Conclusions This study shows that the eK+ concentration could predict the risk of PRHK in deceased LT. Further prospective studies are warranted to clarify these associations.